Implementation Of Protection For Persons With Disabilities Based On Human Security In Papua Province - Aria Aditya Setiawan; Petrus Kanisius Farneubun; Albertina Nasri Lobo (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the implementation of protection for persons with disabilities in Papua Province based on the Human Security approach. The research aims to analyze the extent to which Human Security principles have been applied in disability protection policies, the impact of these policies on increasing the social capital of persons with disabilities, and the challenges faced in their implementation. This study uses a descriptive qualitative method through documentation studies, in-depth interviews, and observation, with data analyzed using the Miles and Huberman model. The findings show that Papua Province has adopted disability protection policies through Regional Regulation No. 5 of 2013 concerning the Protection of Persons with Disabilities, as a follow-up to Indonesia’s ratification of the UN Convention on the Rights of Persons with Disabilities (UNCRPD). The implementation of these policies reflects several dimensions of Human Security, including economic, personal, community, and political security. The policies have contributed positively to increasing social participation, educational access, employment opportunities, institutional strengthening, and the empowerment of persons with disabilities. However, major challenges remain, including limited disability-friendly infrastructure, insufficient budget allocation, low public awareness, weak inter-agency coordination, and the incompatibility between national regulations and Papua’s socio-cultural conditions. The study concludes that a stronger synergy between government, communities, and the private sector is necessary to create more inclusive, sustainable, and human-centered protection for persons with disabilities in Papua Province.